Loss of AMPK activation promotes the invasion and metastasis of pancreatic cancer through an HSF1‐dependent pathway. Issue 10 (29th August 2017) - Chen, Ke; Qian, Weikun; Li, Jie; Jiang, Zhengdong; Cheng, Liang; Yan, Bin; Cao, Junyu; Sun, Liankang; Zhou, Cancan; Lei, Meng; Duan, Wanxing; Ma, Jiguang; et al.
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is a lethal malignancy with a mortality rate that closely parallels its incidence rate, and a better understanding of the molecular and cellular mechanisms associated with the invasion and distant metastasis is required. Heat shock factor 1 (HSF1) is a very highly conserved factor in eukaryotes that regulates the protective heat shock response. Here, we show that HSF1 is abnormally activated in pancreatic cancer. The knockdown of HSF1 impaired the invasion and migration and epithelial–mesenchymal transition (EMT) of pancreatic cancer cells in vitro ; however, the upregulation of HSF1 showed the opposite effects. In vivo, the pharmacological inhibition of HSF1 significantly reduced the tumor burden, decreased the incidence of invasion, and prolonged the overall survival of transgenic mice harboring the spontaneous pancreatic cancer. We suggest that the loss of AMP‐activated protein kinase (AMPK) activation mediates the abnormal activation of HSF1 based on the findings that phospho‐HSF1 (p‐HSF1) was highly expressed in human PDAC tissues with a low expression of p‐AMPK and that in those tissues with a high p‐AMPK expression, the level of p‐HSF1 was decreased. The in vivo and in vitro activation of AMPK impaired the activity of HSF1, and HSF1 mediated the effects of the AMPK knockdown‐induced pancreatic cancer invasion and migration. Our study revealed a novel mechanism by which the loss of AMPK activation amplifies the activity of HSF1 to promote the invasion and metastasis of pancreatic cancer. Abstract : The molecular and cellular mechanisms associated with the invasion and distant metastasis of pancreatic ductal adenocarcinoma (PDAC) are still not fully elucidated. Here, we show that abnormally activated heat shock factor 1 (HSF1) promoted the epithelial–mesenchymal transition, invasion, and metastasis of PDAC. AMP‐activated protein kinase (AMPK), which was inactivated in PDAC, mediated the abnormal activation of HSF1. Our study revealed a novel mechanism suggesting that the loss of AMPK activation amplifies the activity of HSF1 to promote the invasion and metastasis of pancreatic cancer.